Determinants of export intensity and propensity among small and medium-sized enterprises: The case of the Philippines - Philip Tua\~no; George Manzano; Isabela Villamil (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2014)
The small and medium enterprise (SME) sector in the Philippines is a significant group within the economy in terms of firm numbers and total employment. However, the SME sector's share of exports is disproportionately small, which raises considerable policy concerns. Prompted by the aforementioned policy issue, this study assesses the different factors that affect SME decisions (a) to export (propensity) and (b) on how much to export (intensity), i.e., export performance. The study utilizes data from the World Bank enterprise surveys, which contain subjective elements concerning the impediments to conducting business in general, e.g., concerns regarding labour regulations, shipping etc. Using a Heckman selection model, the study finds that firm size is a robust determinant, both of export propensity and intensity. It also suggests that while labour productivity is important in determining the value of firm exports, there are certain firm qualities that are important to the initial export decision, such as foreign ownership and the presence of informal competition. Finding such determinants of SME export intensity and propensity provides the direction for policy discussions.
Keywords: F23; L25; 330; Small and medium-sized enterprises; export; propensity; intensity; performance; the Philippines; manufacturing